(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the surgical management of thyroid disease. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Otorhinolaryngology and Head& Neck Surgery Department Sandeman (Provincial) Hospital, Quetta from March 2014 to May, 2016. Materials and Methods: This study included 43 patients of thyroid disease of the afore-said period. Medical records of patients were reviewed retrospectively and results were analyzed. Results: The mean age of the patients was 34.95±11.97 (S.D) years and male to female ratio was 1:7.6.The benign lesions were 88.63% and malignant lesions were 11.63%. Simple multi nodular goiter was 39.53% and was most common cause of thyroid enlargement. Near total thyroidectomy was performed in 34.88% and total thyroidectomy in 30.23%. Other procedures performed were lobectomy with isthmusectomy (27.91%), subtotal thyroidectomy (4.65%) and total thyroidectomy with central compartment lymph node dissection (2.33). The overall complication rate was 16.29%. Hypocalcemia was most frequent complication followed by recurrent laryngeal nerve palsy. Conclusion: Thyroid disorders are more common in females. Simple multinodular goiter is the most frequent cause of thyroid enlargement. Near total thyroidectomy seems to be optimal procedure for benign thyroid lesions while total thyroidectomy for malignant lesions. Hypoparathyroirdism and recurrent laryngeal nerve palsy are common complications.